The Influence of Achievement Motivation and Work Discipline on Employee Performance: Study at One of The Future Companies in The City of Bandung - Irma Lestari; Soelaeman Sukmalana; Asep Rochyadi Suherman; Titi Titi (Majalah Bisnis & IPTEK, 2023)
Kidney The objective of this study is to ascertain and scrutinize the impact of achievement motivation on the performance of employees, the impact of work discipline on employee performance, and the impact of motivation and work discipline on employee performance. The employed research methodology entails the utilization of both descriptive and verification techniques. The present investigation concerns the populace of laborers affiliated with a forthcoming enterprise situated in Bandung. The study's sample size encompasses 124 respondents, who select through the Slovin technique. The process of gathering information is executed via questionnaires, whereas data examination is conducted through path analysis. The statistical analysis results indicate that Achievement Motivation (X1) exerts a direct impact of 28.4%, an indirect impact through competence (X2) of 17.2%, and a cumulative impact of 45.6%. The variable denoted as work Discipline (X2) exerts a direct impact of 14.4% and an indirect impact through achievement Motivation (X1) of 17.2%, resulting in a cumulative impact of 31.5%. The present study reports that the percentage value of the coefficient of determination (R2) signifies the extent to which the performance variable is determined by the independent variables, namely Achievement Motivation (X1) and Work Discipline (X2). The obtained R2 value is 77.1%. The present study did not investigate certain performance-affecting factors; however, their influence was suggested by the observed value of ɛ = 0.229, equivalent to 22.9%. Thus, it infers that the presence of Achievement Motivation and Work Discipline results in a favorable and noteworthy impact on the overall performance of employees.